2018
DOI: 10.18632/aging.101362
|View full text |Cite
|
Sign up to set email alerts
|

Effects of senescence and angiotensin II on expression and processing of amyloid precursor protein in human cerebral microvascular endothelial cells

Abstract: The present study was designed to determine the effects of senescence and angiotensin II (Ang II) on expression and processing of amyloid precursor protein (APP) in human brain microvascular endothelial cells (BMECs). Senescence caused a decrease in APP expression thereby resulting in reduced secretion of soluble APPα (sAPPα). In contrast, β-site APP cleaving enzyme (BACE1) expression and production of amyloid β (Aβ)40 were increased in senescent endothelium. Importantly, in senescent human BMECs, treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…Emergent evidence suggests that Ang II impacts amyloid precursor protein (APP) metabolism in cerebral microvascular endothelial cells through the Ang II type 2 receptor (AT2R) [65]. The AT2R-mediated action of Ang II on senescent primary human brain microvascular endothelial cells aggravated senescence-induced distortion of APP processing, adding therefore to the development of cerebral amyloid angiopathy and consequently to Alzheimer's disease pathology [65]. Further experiments are warranted to investigate AT2R involvement as a potential therapeutic target for Alzheimer's disease management.…”
Section: Other Novel Ras Components: At2 and At4 Receptorsmentioning
confidence: 99%
“…Emergent evidence suggests that Ang II impacts amyloid precursor protein (APP) metabolism in cerebral microvascular endothelial cells through the Ang II type 2 receptor (AT2R) [65]. The AT2R-mediated action of Ang II on senescent primary human brain microvascular endothelial cells aggravated senescence-induced distortion of APP processing, adding therefore to the development of cerebral amyloid angiopathy and consequently to Alzheimer's disease pathology [65]. Further experiments are warranted to investigate AT2R involvement as a potential therapeutic target for Alzheimer's disease management.…”
Section: Other Novel Ras Components: At2 and At4 Receptorsmentioning
confidence: 99%
“…Moreover, physiologic expression of APP in brain ECs is required to maintain normal eNOS expression, leading to the suggestion that disturbed metabolism of APP in mutant APP models of AD may lead to impaired expression of eNOS and vascular dysfunction [79]. Furthermore, senescence of human brain ECs was accompanied by increased levels of BACE-1 and Aβ 1−40 , and the latter was reversed by treatment with a BACE-1 inhibitor [80]. And absence of eNOS increased Aβ pathology in Tg-5xFAD mice [81].…”
Section: Discussionmentioning
confidence: 99%
“…While the pathological outcome of APP dysregulation is mainly associated to its overexpression, recent studies showed that APP expression levels tend to decrease with age [ 59 , 60 ], and APP-knockout mice show age-dependent cognitive deficit and impaired locomotor activity [ 61 , 62 ]. Moreover, senescent brains showed an increase of amyloidogenic processing mediated by BACE1 [ 63 ], indicating that amyloid-β peptides accumulation is not necessarily associated with APP overexpression.…”
Section: Discussionmentioning
confidence: 99%